EVALUATION OF LIFE SAFETY TECHNICAL FACILITIES FROM FIRE ON APARTEMENT - Vividia, Yemima Sahmura; Harsritanto, Bangun IR (architecture department, Engineering faculty, Universitas Diponegoro, 2019)
Vertical occupancy, especially apartments, began to live the face of the city. Not without reason, housing needs continue to increase sharply as the availability of vacant land is increasingly limited. Occupying an apartment becomes a trend and lifestyle for young people. The reason boils down to productivity. The construction of apartments is usually built close to various activity centers, both business, commercial, education, health to entertainment. The improvement of building construction is not supported by the availability of land that is increasingly limited, especially in the city of Jarakta, making the construction of high-rise buildings anticipate this. The construction of multi-story buildings also increases the risk of fire. In 2018, according to him, there were at least 1,078 recorded disaster events throughout 2018. Head of the Jakarta Fire and Rescue Management Agency, Subedjo, said that out of a total of 897 buildings or tall buildings in Jakarta, 280 tall buildings had not yet accomplished the fire protection system (Dinas, 2018).Therefore, this research needs to be done to evaluate the lifesaving facilities and infrastructure in the building. The application of fire safety in buildings can be evaluated regarding to NFPA 101 (2013). Based on NFPA 101A: Guide on Alternative Approaches for Life Safety (2013), there are 12 elements of safety and Regulation of the Minister of Public Works No. 26 / PRT / M / 2008 concerning Technical Requirements of Fire Protection Systems in Building Buildings. The building that became the object of research is one of the buildings in the area of Jakarta mentioned building X and building Y. The variables that are the focus of the research are fire stairs, fire doors, and access roads. Based on the results of the study, the level of reliability of the means of saving lives against fire hazards in building X is equal to 58% and in building Y is 65%.